2005
DOI: 10.1039/b511626k
|View full text |Cite
|
Sign up to set email alerts
|

Cross-metathesis of unsaturated natural oils with 2-butene. High conversion and productive catalyst turnovers

Abstract: The cross-metathesis of synthetic and natural triglycerides containing unsaturated fatty acids with 2-butene can be achieved with high conversion and excellent productive turnovers. These reactions are catalysed by second-generation ruthenium-based olefin metathesis catalysts and can be conducted at -5 degrees C in liquid 2-butene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…For example, in the case of glycerol trioleate ethe-nolysis, the triglyceride of a-decenoic acid is the coproduct. [20][21][22][23][24][25] Although thesec oproducts are interesting bi-or trifunctional molecules with potentially valuable applications,t he overall yield of a-olefins is low,f or example, only 43 %w /w of glycerolt rioleate is converted into the desired high-value LAO. Similarly,m etathesis has been used widely to cleave fatty acid derivatives to lead to unsaturated long-chain a-olefins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of glycerol trioleate ethe-nolysis, the triglyceride of a-decenoic acid is the coproduct. [20][21][22][23][24][25] Although thesec oproducts are interesting bi-or trifunctional molecules with potentially valuable applications,t he overall yield of a-olefins is low,f or example, only 43 %w /w of glycerolt rioleate is converted into the desired high-value LAO. Similarly,m etathesis has been used widely to cleave fatty acid derivatives to lead to unsaturated long-chain a-olefins.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major application of the cross metathesis of vegetal oils was presented by Patel et al in 2005. They showed that the cross-metathesis of synthetic and natural triglycerides containing unsaturated fatty acids with 2-butene can be achieved with high conversion and excellent productive turnovers [18]. These reactions are catalysed by second-generation ruthenium-based olefin metathesis catalysts and can be conducted at -5°C in liquid 2-butene.…”
Section: X Scheme 14 Alkene Ruthenium Catalysts Bearing An Ionic Tagmentioning
confidence: 98%
“…Hoveyda-Grubbs 2 nd generation catalyst was chosen as it gave better results in butenolysis reactions in organic solvent compared to Hoveyda-Grubbs 1 st generation catalyst. 18,39,40 Similar to the aforementioned ethenolysis in scCO 2 , the butenolysis was conducted at a pressure of 300 bar at a temperature of 45°C.…”
Section: Butenolysis Of Model Compounds and Microalgae Oilmentioning
confidence: 99%